Pengembangan Perangkat Pembelajaran Model Inkuiri Terstruktur untuk Meningkatkan Keterampilan Komunikasi dan Kreativitas Peserta Didik Kelas V Sekolah Dasar - Randy Bambang Nugraha; Wahono Widodo; Nadi Suprapto (University of Bengkulu, 2022)
[The Development of Structured Inquiry Model Learning Set to Improve the Communication Skills and Creativity of Grade V Elementary School Students]. The latest science learning must contain student-centered activities so they are able to practice communication skills and creativity. This study aims to produce valid, practical, and effective structured inquiry learning sets to improve students communication skills and creativity. This research is an R&D model development research with one group pretest-posttest design and one shot case study design and tested on 20 students of class V SDN Geluran 1. Data obtained through validation, observation, questionnaires, and creativity tests. Validation was carried out by three experts and the reliability was analyzed using Alpha Cronbach. Observations were carried out by two observers. Questionnaries filled out by each student. The results of the creativity test were analyzed using the mean and N-Gain. The results showed that the learning set was very valid with a mean score is 91,97. The observation score shows an increase in each aspect in each meeting. Students responses ranged from 92% to 100%. The average pretest result is 57 with 6 completed. The average posttest result is 85 with 20 completed. The N-Gain score shows 6 students in the high category and 14 students in the medium category. It can be concluded that the students communication skills and creativity can be improved by using structured inquiry learning model.